2016
DOI: 10.1007/s11764-016-0520-0
|View full text |Cite
|
Sign up to set email alerts
|

The unmet emotional, care/support, and informational needs of adult survivors of pediatric malignancies

Abstract: Purpose Describe the prevalence and predisposing factors for potentially modifiable unmet emotional, care/support, and information needs among adult survivors of childhood malignancies. Methods A randomly selected/stratified sample of participants in the Childhood Cancer Survivor Study (CCSS) responded to the CCSS-Needs Assessment Questionnaire (CCSS-NAQ) (n=1189; mean [SD] current age, 39.7 [7.7], range=26–61 years; 60.9% women; mean [SD] years since diagnosis, 31.6 [4.7]). Survivors self-reported demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 50 publications
(54 reference statements)
4
30
1
1
Order By: Relevance
“…endocrine system, heart, bones, cognitive and neurological system and can cause secondary malignancies. Furthermore, CAYAs have a high rate of unmet psychosocial needs that are currently neither regularly assessed nor cared for [89]. Although CAYAs have faced a severe life-threatening disease in the early years of their lives, one third of survivors have a risky health behaviour and an unhealthy lifestyle [32].…”
Section: Discussionmentioning
confidence: 99%
“…endocrine system, heart, bones, cognitive and neurological system and can cause secondary malignancies. Furthermore, CAYAs have a high rate of unmet psychosocial needs that are currently neither regularly assessed nor cared for [89]. Although CAYAs have faced a severe life-threatening disease in the early years of their lives, one third of survivors have a risky health behaviour and an unhealthy lifestyle [32].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found similar deficits in knowledge of treatment and the risk of late effects. [35][36][37][38][39] We examined levels of concern among childhood cancer survivors, which may be distinct from previous studies focused on high levels of worry as a threat to psychosocial well-being. 8,[10][11][12][13][14][15][16] Limited evidence suggests that survivors worry less about general health issues than those without a cancer history but have a higher degree of worry about cancer-specific issues such as recurrence or a new cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many ASCCs live with treatment‐related health consequences including disease recurrence, fertility issues, and other chronic diseases . Psychosocial adjustment is also a significant health concern, being associated with delayed social maturation, academic and employment barriers, psychological disturbances, and health‐risk behaviors such as tobacco and alcohol abuse, inactivity, and obesity . Further, survivor uncertainty and fear of recurrence can interfere with activities of daily living .…”
Section: Introductionmentioning
confidence: 99%